2021
DOI: 10.1016/j.isci.2021.102539
|View full text |Cite
|
Sign up to set email alerts
|

Designing optimal integrated electricity supply configurations for renewable hydrogen generation in Australia

Abstract: Summary The high variability and intermittency of wind and solar farms raise questions of how to operate electrolyzers reliably, economically, and sustainably using predominantly or exclusively variable renewables. To address these questions, we develop a comprehensive cost framework that extends to include factors such as performance degradation, efficiency, financing rates, and indirect costs to assess the economics of 10 MW scale alkaline and proton-exchange membrane electrolyzers to generate hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“… 12 , 13 The hybrid techniques with a combination of more than one optimization technique are also gaining currency to exploit the advantages of two different optimization techniques. 14 The researchers have envisaged the energy need fulfillment of off-grid communities in isolated areas 15 and developing nations. 16 …”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 The hybrid techniques with a combination of more than one optimization technique are also gaining currency to exploit the advantages of two different optimization techniques. 14 The researchers have envisaged the energy need fulfillment of off-grid communities in isolated areas 15 and developing nations. 16 …”
Section: Introductionmentioning
confidence: 99%
“…In the literature, various techno‐economic studies of hydrogen production from solar energy can be found. [ 6–12 ] Broadly speaking, they can be classified into three categories: 1.Modelling of state‐of‐the‐art technologies to obtain an estimate for the current LCOH 2 [ 6,11 ] …”
Section: Introductionmentioning
confidence: 99%
“…In the literature, various techno-economic studies of hydrogen production from solar energy can be found. [6][7][8][9][10][11][12] Broadly speaking, they can be classified into three categories:…”
mentioning
confidence: 99%
“…In November 2019, the Australian federal government launched its National Hydrogen Strategy [12] with the goal of positioning Australia as a major player by 2030. Several other studies have also recognized Australia's potential competitive advantage in the emerging hydrogen economy [14,15,16,17,13].…”
Section: Introductionmentioning
confidence: 99%